Inquiry Scientific Reflections in High School Biology Textbooks in South Sulawesi: A Study of Inquiry-Based Task Design Evaluation - S, Muh Akbar; Susanto, Hendra; Saptasari, Murni (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
Textbook studies require a focused examination, especially regarding the emphasis on inquiry in science education. Despite the widespread adoption of inquiry-based tasks, there is a notable delay in evaluation efforts. The Merdeka and 2013 curriculum actively inquiry approaches in biology learning, emphasizing the imperative role of inquiry in biology textbooks and assignments, warranting thorough evaluation. This research aims to assess learning task quality in high school biology textbooks in South Sulawesi from an inquiry perspective. Employing quantitative descriptive methods and cluster random sampling, textbooks were chosen from representative districts/cities. The most frequently used books from each class were analyzed. A total of 51 inquiry tasks were examined using the Inquiry-based Tasks Analysis Inventory (ITAI), known for its robust validity and reliability. Adapted for this study, results underscore an imbalance in inquiry process skills in one textbook and a prevalence of assignments providing activity guidance, impacting students' opportunities to practice process skills and deepen their understanding of inquiry. The findings carry implications for the limited chances students must practice process skills and enhance their comprehension of inquiry.